In vitro antifungal activity of ketoconazole against clinical isolates of Candida and Cryptococcus spp. - Ukesh CS; Patil SD (International Journal of Life Sciences, 2017)
The incidence of fungal infections has been rising over the past few decades contributing to morbidity and mortality. Antifungal activity of ketoconazole was evaluated against clinical isolates of Candida abicans, C. guilliermondii, C. krusei, C. glabrata, C. parapsilosis, C. stellatoidea, C. tropicalis, C. pseudotropicalis and Cryptococcus neoformans by broth macrodilution, broth microdilution and agar dilution methods. Ketoconazole showed strong antifungal activities against isolated strains of Candida and Cryptococcus. Ketoconazole effectively inhibited C. albicans in the MIC range of 1.25-80 μg/ml by broth micro dilution, 2.5-160 μg/ml by broth macro dilution and 2.5-160 μg/ml by agar dilution method. Candida spp were more resistant to ketoconazole than Cryptococcus neoformans, as C. neoformans was inhibited at lower MIC range of 1.25-40 μg/ml. Agar dilution method showed higher MIC values as compared to broth dilution. The results suggest promising antifungal properties of ketoconazole.